Theory of electrical characteristics for metal-oxide-insulator Schottky barrier and metal-insulator-metal structures - Gupta, H. M. [UNESP]; Morais, Marta B. [UNESP] (AIP Publishing, 1990)
The metal-insulator or metal-amorphous semiconductor blocking contact is still not well understood. Here, the intimate metal-insulator and metal-oxide-insulator contact are discussed. Further, the steady-state characteristics of metal-oxide-insulator-metal structures are also discussed. Oxide is an insulator with wider energy band gap (about 50 Å thick). A uniform energetic distribution of impurities is considered in addition to impurities at a single energy level inside the surface charge region at the oxide-insulator interface. Analytical expressions are presented for electrical potential, field, thickness of the depletion region, capacitance, and charge accumulated in the surface charge region. The electrical characteristics are compared with reference to relative densities of two types of impurities. ln I is proportional to the square root of applied potential if energetically distributed impurities are relatively important. However, distribution of the electrical potential is quite complicated. In general energetically distributed impurities can considerably change the electrical characteristics of these structures.